Character of Beggar in Ali Abbas Hussaini's Fiction - Ullah, Saira Saif; Subhani, Mamuna (sourcecoder, 2023)
Beggars are a different group in society with several reasons for begging. Some suffer from serious health issues. Others beg due to financial hardships, while criminal persons forcefully induct some in organized begging networks. The attitude of our society towards them differ from kindness to distrust, which influenced by our cultural norms and policies. Ali Abbas presented both concepts of the society and the mindset of our culture. In today’s society, several people consider them a threat to the culture. His fictional characters describe the real picture of baggers and the behavior of society towards them. His fiction easily illuminate the complex challenges of society.